The discourse on love and couple relationships of the Communist Party of Peru-Shining Path and its relation to the Peruvian armed conflict - Arrunátegui, Carolina (2022)
This article explores the relation between the love life of the militants of the Peruvian Communist Party-Shining Path (PCP-SL, acronym in Spanish), the terrorist organization with the greatest impact in the history of Peru, and the political life of this party in the context of the armed struggle that began in the 1980's. The following questions are posed: how relevant was the love life of the PCP-SL militants for the political work of the party; how were the intimate and public dimensions articulated in the context of the armed struggle; did the PCP-SL have a discourse or rhetoric on love and couple relationships; and what characterized this speech? Based on the analysis of the essay Love in Communist Society (1973 [1921]) by the Marxist politician Alejandra Kollontai and the review of testimonies of former Shining Path militants, I conclude that the intimate life of PCP-SL members was highly politicized and controlled by the party through a Marxist discourse on love and relationships that turned intimate life into another way of fighting for the revolution.